An in-process robot calibration of serial link manipulator arm based on a 3-D machine vision for minimal invasive orthopedic surgery operation / Muhammad Azmi Ayub … [et al.] - Ayub, Muhammad Azmi; Taib, Mohd Nasir; Jaafar, Roseleena; Omar, Ahmad Maliki; Manurung, Yupiter Harangan Prasada (Research Management Institute (RMI), 2010)
The long term aim of this research project is to design and develop a minimum invasive surgery for femur orthopaedic robot assisted surgery. This requires a fast with high accuracy and quality of the surgery operation. Three main objectives in this research were addressed. These objectives are as follows, • To identify the source of errors in robot trajectory planning during the drilling operation of bone surgery and determine the in-process calibration procedures using a 3 dimensional vision system and 6 degrees of freedom force-toque sensor for compensating the trajectory planning errors. • To calibrate and evaluate the drilling force and torque profile for compensating the errors in robot trajectory planning during the drilling operation. • To determine the performance of the robotic bone drilling operation In order to achieve the abovementioned objectives, the integrated mechatronic research methodology which encompasses development of the hardware and software of the system is very important and has been realised. The hardware components of the mechatronic system consist of two sub-system which are as follows: i. An industrial robotic system ii. A machine vision system The software components of the mechatronic system of the orthopedic surgery consist of two computer algorithms: i. Machine vision computer algorithms for the calibration procedures, ii. Computer algorithm to generate the trajectory planning and to control the motion of the robot. The method of in-process calibrations will be explained, analysed and evaluated. Finally, the performance of the robotic trajectory planning during the bone drilling will also be explained, analysed and evaluated.